Hybrid crystals comprising metal-organic frameworks and functional particles : synthesis and applications - Li, Shaozhou (2015)
Hybrid crystals containing encapsulated functional species exhibit promising novel physical and chemical properties. The realization of many properties critically depends on the selection of suitable functional species for incorporation, the rational control of the crystallinity of the host materials, and the manipulation of the distribution of the encapsulated species; only a few hybrid crystals achieve this. Here, a novel synthetic method enables the encapsulation of functional species within crystalline metal–organic frameworks (MOFs). Various kinds of single-crystalline MOFs with incorporated particles are presented. The encapsulated particles can be distributed in a controllable manner, and the hybrid crystals are applied to the heterogeneous catalysis of the reduction of nitroarenes. These findings suggest a general approach for the construction of MOF materials with potential applications; by combining species and MOFs with suitable functionalities, new properties—not possible by other means—may arise.